2018
DOI: 10.1186/s13046-018-0994-x
|View full text |Cite|
|
Sign up to set email alerts
|

LINC01296/miR-26a/GALNT3 axis contributes to colorectal cancer progression by regulating O-glycosylated MUC1 via PI3K/AKT pathway

Abstract: BackgroundLong non-coding RNAs (LncRNAs) emerging as pivotal marker in the procession of cancer, including colorectal cancer (CRC). Abnormal O-glycosylation is a crucial modification during cancer malignancy. The aim of this work is to analyze the alteration of O-glycosylation involved in CRC progression.MethodsqRT-PCR is utilized to screen the differential linc01296 expression in CRC tissues and cell lines. Functionally, CRC cell proliferation, aggressiveness and apoptosis are measured through relevant experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(71 citation statements)
references
References 38 publications
(44 reference statements)
1
70
0
Order By: Relevance
“…LncRNAs was disease‐related through a host of mechanisms such as chromatin modification, transcription, and post‐transcriptional processing (Zhang et al, ), among which miRNA‐like sponge suggested that lncRNA bind to and inhibit miRNAs and therefore control the post‐transcriptional regulation of miRNA on target gene expression (Tay et al, ). For example, LINC01296/miR‐26a/GALNT3 axis contributes to colorectal cancer progression by regulating O ‐glycosylated MUC1 via PI3K/AKT pathway (Liu et al, ). LncRNA‐TUSC7/miR‐224 affected chemotherapy resistance of esophageal squamous cell carcinoma by competitively regulating DESC1 (Chang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs was disease‐related through a host of mechanisms such as chromatin modification, transcription, and post‐transcriptional processing (Zhang et al, ), among which miRNA‐like sponge suggested that lncRNA bind to and inhibit miRNAs and therefore control the post‐transcriptional regulation of miRNA on target gene expression (Tay et al, ). For example, LINC01296/miR‐26a/GALNT3 axis contributes to colorectal cancer progression by regulating O ‐glycosylated MUC1 via PI3K/AKT pathway (Liu et al, ). LncRNA‐TUSC7/miR‐224 affected chemotherapy resistance of esophageal squamous cell carcinoma by competitively regulating DESC1 (Chang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we also demonstrated that TC2N overexpression was signi cantly related to the clinicopathological features in GC and promoted the its development in vitro. Bioinformatic analysis suggested a connection between TC2N and a series of genes related to human cancer and other diseases, such as CATSPERB, a novel transmembrane protein playing role in the eld of reproduction [34], GALNT3, proved to play important roles in different cancers [35][36][37] and RBM47, reported to inhibit tumor progression in lung, breast and colon cancer [38][39][40]. These evidences further veri ed the potential role of TC2N in GC from another aspect.…”
Section: Discussionmentioning
confidence: 72%
“…As mentioned above, an electronic database search identified 113 literatures according to the search strategy. After a full assessment of these researches, a total of 11 articles21–26 28 31–34 that reported the possible functions or pathways of LINC01296 in human solid malignant tumours were included. Following a summary of the functions and pathways of LINC01296 among the articles, we showed a concise overview of the functionality of LINC01296 in figure 6.…”
Section: Resultsmentioning
confidence: 99%